2012
DOI: 10.3758/s13414-012-0304-1
|View full text |Cite
|
Sign up to set email alerts
|

Increased spatial salience in the social Simon task: A response-coding account of spatial compatibility effects

Abstract: A spatial compatibility effect (SCE) is typically observed in forced two-choice tasks in which a spatially defined response (e.g., pressing a left vs. a right key) has to be executed to a nonspatial feature of a stimulus (e.g., discriminating red from green) that is additionally connoted by a spatial feature (e.g., the stimulus points to the left or the right). Responses are faster and more accurate when the response side and the spatial stimulus feature are compatible than when they are incompatible. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
68
2

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(77 citation statements)
references
References 34 publications
(88 reference statements)
7
68
2
Order By: Relevance
“…In contrast to earlier, decidedly social interpretations of the JSE (Sebanz et al, 2003), more recent findings suggest that the effect reflects the spatial coding of the participant's own action with respect to any other, sufficiently salient event (Dittrich, Rothe, & Klauer, 2012;Dolk et al, 2013). Obviously, the presence of another person is particularly salient and, thus, likely to induce spatial response coding and a reliable JSE, but there is no reason to exclude the possibility that nonsocial events, like a rhythm-producing metronome, can also produce a JSE (Dolk et al, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…In contrast to earlier, decidedly social interpretations of the JSE (Sebanz et al, 2003), more recent findings suggest that the effect reflects the spatial coding of the participant's own action with respect to any other, sufficiently salient event (Dittrich, Rothe, & Klauer, 2012;Dolk et al, 2013). Obviously, the presence of another person is particularly salient and, thus, likely to induce spatial response coding and a reliable JSE, but there is no reason to exclude the possibility that nonsocial events, like a rhythm-producing metronome, can also produce a JSE (Dolk et al, 2013).…”
Section: Discussioncontrasting
confidence: 88%
“…Whereas the action co-representation account speaks to the ability to integrate one's own and others' behaviors, the social attribute that drives this account has been challenged (Dittrich, Dolk, Rothe-Wulf, Klauer, & Prinz, 2013;Dittrich, Rothe, & Klauer, 2012;Dolk et al, 2011;Dolk, Hommel, Prinz, & Liepelt, 2013a;Guagnano, Rusconia, & Umiltá, 2010;Hommel, Colzato, & van den Wildenberg, 2009;Liepelt, 2014). Dolk et al (2013a), for instance, demonstrated that a salient, nonsocial feature in the visual field is sufficient to elicit a correspondence effect even without a co-actor.…”
Section: Action Co-representation Vs Referential Codingmentioning
confidence: 96%
“…Dolk et al concluded that active participation of a co-actor is not necessary for the go-nogo correspondence effect to occur. Rather, any external event that is salient and provides a spatial reference frame relative to which the participant codes her or his own response as left or right is sufficient to elicit a correspondence effect (the referential coding account; see also Dittrich et al, 2012Dittrich et al, , 2013Dolk, Liepelt, Prinz, & Fiehler, 2013b;Guagnano et al, 2010;Liepelt, 2014).…”
Section: Action Co-representation Vs Referential Codingmentioning
confidence: 99%
“…Recently, however, an increasing number of studies have challenged the idea of action/task co-representation by demonstrating that joint SCEs can be elicited via social and nonsocial events (e.g., by another agent or inanimate object; Dittrich, Rothe, & Klauer, 2012;Dolk, Hommel, Colzato, Schütz-Bosbach, Prinz, & Liepelt, 2011;Dolk, Hommel, Prinz, & Liepelt, 2013;Dolk, Liepelt, Prinz, & Fiehler, 2013;Guagnano, Rusconi, & Umiltà, 2010). To simplify matters, we will term this approach the spatial-coding account in the remainder of this article, although the ideas of spatial coding formulated in previous works have focused on different aspects.…”
mentioning
confidence: 99%